Chiroptera (Chordatta: Mammalia) capturados em Belo Horizonte, Minas Gerais, 1999 a 2003. - Leonardo Victor de Knegt (2003)
After a literature survey, it was found that, to date, the Chiroptera in Belo Horizonte were represented by three families (Phyllostomidae, Vespertilionidae and Molossidae), 18 genera and 24 species. With the aim of increasing knowledge of bat species present in the municipality as well as their distribution in urban and some characteristics of their reproductive cycle, a survey was conducted between 1999 and 2003. The study area, located at an altitude of 852.3 m above the sea level, 19 ° 56'S latitude and 43 ° 57 'The longitude was divided using the nine Regional Administrative City Hall. For the collection of species, there were two catches Regional home, one dry and one rainy season, and a search for possible shelter in a house of the Regional.